Leaf toughness increases with tree height and is associated with internal leaf structure and photosynthetic traits in a tropical rain forest - Kenzo, Tanaka; Mohamad, Mohizah; Ichie, Tomoaki (Frontiers in Forests and Global Change, 2022)
Although leaf toughness is an essential plant adaptation to herbivore pressure and environmental stress, the relationships of leaf toughness with leaf anatomy and photosynthetic traits, and its spatial variations within tropical rainforests, remain poorly understood. We measured these traits in 103 tree species belonging to 27 families from the canopy to understory using a canopy crane system in a tropical rainforest in Sarawak, Malaysia. We focused on the leaf anatomical trait of bundle-sheath extensions (BSEs) around the vascular bundle due to their diverse ecophysiological functions. We divided the trees into heterobaric species with BSEs and homobaric species lacking BSEs, to investigate the relationships of leaf toughness with tree height, leaf functional traits such as carbon (C) and nitrogen (N) content, thickness, leaf mass per area (LMA) and the maximum photosynthetic rate (Pmax). Leaf toughness, LMA, thickness and C and N contents increased with height regardless of BSE presence. Heterobaric leaves had greater toughness than homobaric leaves, whereas leaf thickness, LMA and C were similar between the two leaf types throughout the height gradient. We found that standardized toughness per thickness or C was greater in heterobaric species, as BSEs consist mainly of fibrous tissue. Pmax was higher for heterobaric than homobaric leaves in the upper canopy presumably due to the functions of BSEs, including water conductivity, but did not differ with plant type in the lower layers. In other words, heterobaric species efficiently exploit the advantages of tougher leaves and higher Pmax by having BSEs. The increased proportion of heterobaric species, with their tougher leaves and higher Pmax, in the upper canopy is consistent with adaptation to physically stressful conditions in the tropical rainforest canopy, including high herbivore pressure and strong light.